0243 Sleep-Wake Patterns during Infancy are Associated with Gut Microbial Community Structure in Toddlerhood. (12th April 2019) - Petrov, Megan E; Whisner, Corrie M; McCormick, David; Todd, Michael; Reifsnider, Elizabeth
Abstract: Introduction: Sleep loss and circadian misalignment are hypothesized to be stressors that have the potential to influence the gut microbiome (GM); however, there are limited human studies on these relationships and none have been conducted among infants and toddlers. The aim of this study was to examine differences in the gut microbiota (GM) composition in toddlerhood by sleep-wake patterns that occurred in infancy. Methods: Pregnant, obese Latina women recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children program took part in a RCT designed to provide education on infant development to prevent incidence of infant overweight. The intervention was delivered across infancy until 12 months. Participants were followed until 36 months. At one, 6, and 12 months, mothers completed the Brief Infant Sleep Questionnaire. Among a sub-set of children (n=36), feces were collected at 36 months. Sleep duration, timing, and diurnal/nocturnal patterning were examined in relation to GM diversity metrics using Kruskal-Wallis and PERMANOVA comparisons. Multiple comparison-adjusted, LDA Effect Size (LEfSe) analyses were conducted to examine differences in GM taxa abundance according to sleep variables. Results: GM diversity at 3 years varied by aspects of infant sleep during the first 12 months of life. How evenly taxa proportions in the GM community were distributed was significantly lower (H=4.63, p =0.03) among children with later bedtimes (≥10:00 PM) at 1 month of age. Other within-sample (unique taxa) and between-sample (shared taxa) community diversity metrics did not differ at 3 years by sleep measures obtained in infancy. LEfSe analysis of microbial taxa revealed significant differential abundance distributions of health and disease-associated microbes for sleep duration, number of naps, and bedtimes >10:00 PM at 6 and 12 months (all p <0.05). Conclusion: These are some of the first data indicating that sleep behaviors in early infancy may have an impact on shaping the GM through 3 years of age. Further work is needed to understand temporal changes in microbial taxa in the first year of life and how changes influence health risks in childhood. Support (If Any): NIDDK/NIH R01DK096488